An Empirical Examination of Voluntary Development Activities of Employees. (January 2022) - Deosthali, Kanchan V.; Johnson, Richard D.
This study develops and empirically examines a model of voluntary employee self-development behaviours and presents a unique lens for the study of self-development behaviours that integrates the disparate social exchange and motivational models currently applied in the management and training motivation literature. Specifically, the current model utilizes the Theory of Planned Behavior (TPB) as a guiding framework in the combination and expansion of these streams to create an integrated model. This model was validated using a survey of 203 employees. Structural Equation Modelling (SEM) was used to analyse the data. The results indicated support for nine out of eleven theorized relationships in the model, and the new model explained more variance in self-development behaviours (38%) than either lens: the social exchange (8.5%) or the motivational (19%). Thus, the results indicate there is important value in integrating the lenses. Implications for research and practice are also discussed.